Direct synthesis of amides from amines using mesoporous Mn-SBA-12 and Mn-SBA-16 catalysts - Kumar, Anuj; Nepak, Devadutta; Srinivas, Darbha (Catalysis Communications, 2013)
Manganese incorporated SBA-12 and SBA-16 catalyze the tandem reaction of aliphatic primary amine, aerial oxygen and ammonia solution at moderate conditions producing amide in yields as high as 50 mol%. The Mn-SBA-12 and Mn-SBA-16 catalysts with Si/Mn output molar ratio in the range 230 to 748 were prepared by the direct hydrothermal synthesis method and characterized. Weak acidity and Mn in +3 oxidation state are the key factors enable the synthesis of product amide in high yields. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aerial oxidation; Amide synthesis; Benzyl amine; Manganese incorporated SBA-12 and SBA-16; Mesoporous Mn-silica catalyst

Effect of alkali and alkaline earth metal ions on benzyl alcohol oxidation activity of titanate nanotube-supported Au catalysts - Nepak, Devadutta; Srinivas, Darbha (RSC Advances, 2015)
Sodium titanate nanotubes (NaTNTs) were prepared by alkali treatment of anatase titania. They were then ion-exchanged with alkali and alkaline earth metal ions to get ATNTs (A = Li+, K+, Cs+, Mg2+, Ca2+, Sr2+ and Ba2+). Gold (1-5 wt%) was supported on these nanotubes by a deposition-precipitation method and investigated as a catalyst for the selective oxidation of benzyl alcohol with air/molecular oxygen (1 atm) under solvent-and alkali-free conditions. Detailed characterization by X-ray powder diffraction, high resolution transmission electron microscopy, N-2-physisorption, diffuse reflectance UV-visible spectroscopy, X-ray photoelectron spectroscopy and CO2-temperature-programmed desorption techniques revealed that the basicity of the catalyst influences the uptake, mean particle size, electronic properties and oxidation activity of the supported gold. Benzaldehyde formed with a selectivity of about 99%. The catalytic activity (turnover frequency) was found to have a direct relationship with the basicity and an inverse relationship with the Au particle size. Among the catalysts investigated, Au/BaTNTs, having higher basicity, smaller Au particles and higher metal dispersion, showed enhanced catalytic activity than the other Au/ATNT catalysts. Pd addition to Au leading to Au-Pd/BaTNTs increased the activity (TOF) but lowered the selectivity for benzaldehyde (80 wt%). Titanate nanotubes donate electron density to Au particles, yielding electron rich Au ions, which are responsible for activating molecular oxygen and oxidizing benzyl alcohol. Au/BaTNTs, having higher basicity and lower size Au nanoparticles than the other Au/ATNT, activates molecular oxygen more easily and thereby enhances the catalytic activity.

Selective aerobic oxidation of alcohols over Au-Pd/sodium titanate nanotubes - Nepak, Devadutta; Darbha, Srinivas (Catalysis Communications, 2015)
catalytic application of Au-Pd nanoparticles supported on sodium titanate nanotubes (NaTNTs) for liquid-phase aerobic oxidation of alcohols is reported, for the first time. This reaction occurs at 80-120 degrees C, 1 atm and solvent-/alkali-free conditions yielding the corresponding carbonyls in high selectivity. This catalyst was reusable and found to be more active/selective than the corresponding monometallic Au and Pd catalysts and Au-Pd/TiO2. Higher dispersion, smaller particle size and higher amount of electron density at gold are the causes for the superior activity of Au-Pd/NaTNT catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Alcohol; Bimetallic Au-Pd catalyst; Sodium titanate nanotubes; TiO2

Spectroscopy and catalytic activity study of gold supported on barium titanate nanotubes for styrene epoxidation - Nepak, Devadutta; Srinivas, Darbha (Applied Catalysis A-General, 2016)
Gold (0.5-5 wt.%) supported on barium titanate nanotubes (Au/BaTNT) were prepared, characterized and for the first time, investigated as catalysts for selective oxidation of styrene with oxygen (O-2 or H-2 + O-2) and peroxides (H2O2 or TBHP). Conversion of styrene enhanced when H-2 was co-added to O-2 in the reactions. Au/BaTNT activated O-2 and H-2 and produced H2O2 in situ for use in oxidations. Peroxides were found better oxidants than O-2. At optimized conditions, styrene oxide selectivity of 80.1 wt.% at styrene conversion of 60.5 wt.% was achieved over Au(1 wt.%)/BaTNT using TBHP. Au particles (5.0-7.4 nm) were dispersed and decorated on the walls of BaTNT. They exhibited superior performance to the known Au catalysts in styrene oxidation. Reactive oxygen species formed during oxidation reactions were followed with in situ spectral characterizations (diffuse reflectance UV-vis and FT -Raman). Au/BaTNT was reusable in four recycles with little loss in catalytic activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; reactive oxygen species; spectroscopy; Styrene Oxidation; Titanate nanotubes

Dry reforming of methane in DBD plasma over Ni-based catalysts: influence of process conditions and support on performance and durability - Ray, Debjyoti; Nepak, Devadutta; Janampelli, Sagar; Goshal, Partha; Subrahmanyam, Ch (Energy Technology, 2019)
The conversion of greenhouse gases, H-2 and CO selectivity, H-2/CO ratio, and carbon formation in the dry reforming reaction over Ni-supported ZSM-5, Al2O3, and TiO2 are tested under thermal, plasma, and plasma-thermal conditions. It is observed that the dielectric nature, specific surface area, and acid-base properties of the support influence the performance during the DRM reaction. Typical results indicate that the best activity and syngas yield are achieved with 15Ni/Al2O3 under plasma conditions, possibly due to the high dielectric constant and surface area of Al2O3 and nanosize of Ni. In the thermal condition, the highest conversion of 73% and 68% for CH4 and CO2, respectively, is achieved over 15Ni/ZSM-5 at 500 degrees C. Plasma-assisted thermal conditions provide the highest conversion due to the activation of reactants and their partial conversion in the plasma zone before entering into the catalytic zone. The plasma-assisted thermocatalytic conversions of CH4 and CO2 reach the best values of 76% and 71%, respectively, on 15Ni/ZSM-5. Under the same conditions, 68% and 65% conversion of CH4 and CO2, respectively, is achieved with 15Ni/Al2O3 where the selectivity for H-2 and CO is 45% and 58%, respectively.
Keywords: DBD plasma; Dry reforming; reaction conditions; supported catalysts; Syngas